THE EFFECTIVENESS OF USING DESIGNED COASTAL AREA MEDIA FOR MATHEMATICS LEARNING - Zuhri D; Sehatta S (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Abstract: The meaning of numbers, often referred to as Number Sense, is very important for students to understand, especially in elementary school. Correspondingly, elementary school students who are new to numbers must be given real experiences as a means of building an understanding of the meaning of numbers. Related to that, this study aimed to investigate the understanding of grade I elementary school students who were taught using the designed coastal area media. The subjects of this study included 2 elementary schools with a total of 42 subjects located on the coast. The purpose of this study was to investigate the effectiveness of learning and its impact on number sense. The results of the data analysis showed that the effectiveness of using the designed coastal area media for mathematics learning was in the Good category. Moreover, the students' understanding of the meaning of numbers after the treatment significantly increased by 21.3%.Keywords: